Monkeypox virus infection and myocarditis: A review of current evidence and possible pathogenesis - Ahmed, Sirwan K.; Dabou, Eman A.; Abdelsamad, Shaimaa; Mohamed, Mona G.; Chandran, Deepak; Chakraborty, Sandip; Emran, Talha B.; Dhama, Kuldeep (Narra J, 2023)
The recent spread of the monkeypox virus (MPXV), causing monkeypox (mpox), to non-endemic areas, and the atypical and unusual clinical manifestations observed during its 2022 outbreak has focused international interest on the clinical features of the disease. Mpox is usually a self-limiting disease with mild symptoms with common manifestations, including fever and skin lesions; however, severe manifestations could occur in some vulnerable groups (children and those with impaired immune systems) and may present multisystem complications and fatal outcomes. In most cases, a fever is the first sign of disease, followed by the development of various inflammatory lesions on the skin, such as vesiculopustular rashes and ulcers. Pneumonitis, encephalitis, keratitis, secondary bacterial infections, acute kidney injury, and myocarditis are all possible outcomes of the infection. Myocarditis has been reported to be caused by orthopoxviruses, and it is a serious condition of which its pathophysiology is little understood. Recent reports have indicated myocarditis with cardiac involvement as a possible atypical and unusual consequence of the MPXV infection during present outbreak. This review provides an overview of the clinical manifestations of mpox with a special focus on its effects on the heart, including myocarditis. The evidence of the myocarditis in mpox patients and its possible pathogenesis are discussed.